Branding dan Kelanggengan Merek: Studi pada Public Relations Kusuma Sahid Prince Hotel Solo - Anita Ratna Sari; Eny Susilowati (UIN Raden Mas Said Surakarta, 2021)
The management of Kusuma Sahid Prince Hotel as one of heritage hotels has its own challenges to attract customer interest in the midst of competition for a number of hotels in Solo, one of which is about branding. This study aims to describe the branding of